ANALISIS KADAR MERKURI (Hg) DALAM SEDIAAN HAND BODY LOTION WHITENING PAGI MEREK X, MALAM MEREK X, DAN BLEACHING MEREK X YANG TIDAK TERDAFTAR PADA BPOM - Wijaya, Fransisca (University of Surabaya, 2013)
Abstract â X brand morning whitening body lotion, X brand night whitening bodylotion, and X brand bleaching unregistered to National Agency of Drugs andFoods Controls (BPOM) are widely used for skin whitening. This research wascarried out to analyze mercury (Hg) level which could possibly be found in thepreparations. Mercury (Hg) should not be used as skin whitening since it can beaccumulated in the body in the long run and eventually can be toxic and damagebody organs. Organoleptic test was conducted using miscibility test got fromPharmaceutics The Science of Dosage Form Design to determine emulsion typesof each preparation. The results showed that the preparations used had emulsiontype of oil in water (o/w). The mercury analysis used the method adopted from2005âs AOAC (Official Methods of Analysis of AOAC International). The studyusing ICPS (Inductively Coupled Plasma Spectrometer) showed linearity resultswith r = 0.9993 and Vxo = 2.02%; wave length used was ? = 253.652 nm; LLOD(Lower Limit of Detection) and LLOQ (Lower Limit of Quantitation) values were0.25 ppm and 0.84 ppm; CV (Coefficient of Variation) for each preparation was0%; 0.28%; 0.26%; recovery % value for mercury (Hg) in each preparation rangefrom 80.30-101.0%; 80.5-98.5%; 80.25-98.5%. the overall findings implied thatthis method meets the requirements in terms of linearity, selectivity, precision,LLOD, LLOQ, and accuracy.